Analyzing the cost-effectiveness of enhancement approaches for rehabilitating water distribution network - Abdel Rahman Mohamed Ismail, Farouk Abdel Mageed Rady (2021)
Sustainable water management has been a trending goal in the world. Non-revenue water (NRW) is one of the forms of water loss. There is a tremendous amount of NRW, especially in developing countries. The real losses represent the more significant portion of the NRW. These losses negatively affect the economy and formulate a barrier towards reaching water sustainability. Therefore, the aim of the study was to that reduce NRW. A systematic review was first conducted to find the relevant techniques and methods for rehabilitating water distribution networks (WDN), which is one of the methods to reduce NRW and to achieve the research aim which is reducing the NRW, after identifying the WDN rehabilitation approaches, a questionnaire survey in Malaysia and Egypt was carried through five months period from June 2020 to October 2020. The main aim of the questionnaire survey was to identify cost-effective enhancement approaches. A total of 109 respondents from Malaysia and 67 respondents from Egypt, which means a total of 176 respondents were collected and analyzed. The sample size is suitable as most of the targeted population are among the managers and project managers with at least three years of experience in the WDN field. The population was determined based on the top companies and water authorities as the research focuses on advanced WDN rehabilitation enhancement approaches. Then, Cronbach’s alpha, mean score ranking, normalization value, and agreement analysis were carried in the data analysis phase. The results show that cost-effective enhancement approaches are programming, models, supervisory control and data acquisition (SCADA), and twin digital. Additionally, the data from Malaysia suggest two more cost-effective enhancement approaches: zoning network and genetic algorithm. These two techniques might possess great potential for other developing countries, such as Egypt. Then finally, after identifying the cost-effective approaches, a comparison between the cost-effective approaches between Malaysia and Egypt was done. Choosing the right technique can help industry practitioners maximize the benefits of WDN rehabilitation. The comparison would help the researchers and industry participants to adopt and further develop the suggested approaches. The discussion of the WDN enhancement rehabilitation approaches can help in adapting them from other countries in the future. Proper WDN rehabilitation supports NRW reduction, which mainly helps move towards sustainable water management in developing countries. Keywords: Sustainable development, water losses, Non-revenue water (NRW), Water distribution network (WDN), Rehabilitation of WDN